STUDENTS’ WRITING DIFFICULTY IN COMPOSING A DESCRIPTIVE TEXT (A Quantitative Study of the First Year Students at STKIP Persada Khatulistiwa Sintang) - Wa Ode Ritna Yuniyr Ullah (STKIP Persada Khatulistiwa Sintang, 2018)
The fact that writing was considered as difficult for most students still remained an unresolved issue. Yet, some educators still continued disregarding what was going on with students’ writing difficulty to promote appropriate way in their teaching of writing. Thus this study was aimed at finding out students’ writing difficulty in composing a descriptive text of the FirstYear Students at STKIP Persada Khatulistiwa Sintang. This study employed quantitative descriptive analysis to describe students’ writing difficulty. One class of first year students of English Language Study Program took part in this study. The data were gathered through writing test that was done on November 6th,2017. The finding showed that students had significant difficulty in composing a descriptive text. It was proved by the mean score of students’ writing quality, i.e. 46 or classified as very poorbased on the criteria suggested by Jacob (1981). Therefore, it was imperative for thelecturer in this class to encourage the learners togive more emphasis on itemsseen difficult by the students in composing the text. Keywords: students’ writing difficulty, teaching writing, descriptive text